2020
DOI: 10.1186/s12873-020-00374-3
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of sepsis-associated encephalopathy: epidemiology, clinical features and adverse outcomes

Abstract: Background Sepsis-associated encephalopathy (SAE) is a common complication of sepsis that may result in worse outcomes. This study was designed to determine the epidemiology, clinical features, and risk factors of SAE. Methods This was a retrospective study of all patients with sepsis who were admitted to the Critical Care Medicine Department of Hangzhou First People’s Hospital Affiliated with Zhejiang University School of Medicine from January 2015 to December 2019. Results A total of 291 sepsis patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 30 publications
8
49
1
Order By: Relevance
“…Although the mechanism remains, to a wide extent, unclear, it is estimated that inflammation reaction and oxidative stress might invite an increase in RDW values, and simultaneously, these mechanisms may play a pivotal role in the poor prognosis of SAE [ 27 29 ]. Furthermore, in keeping with previous study, we also unearthed that age was independently associated with 30-day mortality [ 17 ]. It was probably attributable to the fact that elderly patients exhibit a higher risk and mortality from sepsis [ 30 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although the mechanism remains, to a wide extent, unclear, it is estimated that inflammation reaction and oxidative stress might invite an increase in RDW values, and simultaneously, these mechanisms may play a pivotal role in the poor prognosis of SAE [ 27 29 ]. Furthermore, in keeping with previous study, we also unearthed that age was independently associated with 30-day mortality [ 17 ]. It was probably attributable to the fact that elderly patients exhibit a higher risk and mortality from sepsis [ 30 ].…”
Section: Discussionsupporting
confidence: 74%
“…Published study conducted by Chen J et al [ 17 ] indicated that APACHE II and SOFA were independent risk factors for 28-day mortality in SAE patients, which was similar to our findings. A range of previous studies also have found that the mortality rate of sepsis patients is related to higher values of the GCS, SOFA, and the APACHE II score [ 10 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results from multivariate Cox regression analysis demonstrated that baseline APACHE II score, baseline lactic acid level, septic shock, and baseline AFR were independent prognostic factors in septic patients caused by various infection sites. The APACHE II score is extensively used among critically ill patients with sepsis in the ICU, and is accurate for the prognosis, comparable the SOFA score [ 1 , 26 ]. Our results are also consistent with the apparent correlation between the APACHE II score and prognosis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…This association is independent from sedative or analgesic medication use, age, pre-existing comorbidities, ongoing conditions and the duration of mechanical ventilation [45,51]. In most of the previous studies performed in the ICU, a large number of septic patients were included to investigate the link between delirium and long-term cognitive impairment [52].…”
Section: Sepsis-associated Long-term Cognitive Impairmentmentioning
confidence: 99%